A single limnic eruption at the origin of today's large-scale density structure of Lake Kivu. (January 2020) - Hirslund, Finn
Abstract: This work proposes that the mixed zones and haloclines in Lake Kivu are a result of the following changes: A drought triggered a limnic eruption around 4, 000 yBP, which left behind a uniformly mixed lake. Increasing precipitation after the eruption generated the two upper zones by dilution, first by precipitation into the closed lake and subsequently by flushing when the lake overflowed to Lake Tanganyika. Sublacustrine and saline meteoric sources generated the first denser zone below the former holomictic zone from the eruption and later, magmatic CO2 was added to the saline sources, generating a denser bottommost zone. The continuously inflowing sublacustrine sources caused upward movement of the mixed zones in the lake, movements that continue to this day. If not stopped, this movement will in the future bring the gases from the lower strata closer to the surface and thus to the point of preventing utilization of accumulated CH4 . If wanting to prevent future limnic eruptions, this would leave future generations with no other choice than venting the accumulating gases. Seven brown layers from the last 2, 200 years in the sediments at Lake Kivu were thought to result from limnic eruptions. A re-evaluation of existing data indicates that these layers result from plumes of magmatic CO₂ emanating from fissures below the lake and entraining nutrient-laden bottom water to the mixolimnion, thus lowering the strata above the point of plume initiation. At unpredictable times and with unpredictable intensity, these plumes have thus for the last 2, 000 to 3, 000 years kept down the gas laden strata, thus contributing to preventing further abrupt limnic eruptions caused by gas accumulation. In addition, these CO₂ injections at varying depths and of varying intensities likely are a major contributor to onsets and disappearances of precipitating CaCO3 from the mixolimnion reaching the bottom sediments. Highlights: A drought caused level reduction and likely the only limnic eruption of Lake Kivu. Gas plumes were likely behind six other mixing events. Saline inflows and CO₂ injections formed the two denser mixed zones deepest in lake. Precipitation-induced dilution followed by flushing formed the two uppermost zones. Droughts plus tectonic and volcanic events make forecasting the future uncertain. Abstract : A review of sediment core data leads to proposing a drought-induced limnic eruption as being behind the formation of the 4–5 haloclines in Lake Kivu and that CO₂ plumes are not likely to cause catastrophic limnic eruptions, over years to decades they just cause emission of CO₂ from the resulting plumes.